A Fuzzy Logic Based Mppt Controller For Wind-Driven Three-Phase Self-Excited Induction Generators Supplying Dc Microgrid - B.Murali Mohan; M.Pala Prasad Reddy; M. Lakshminarayana (Institute of Advanced Engineering and Science, 2017)
In this paper, a straightforward strategy for tracking the maximum power (MP) accessible in the wind energy conversion system for dc microgrid is proposed. A three-phase diode bridge rectifier alongside a dc-dc converter has been utilized between the terminals of wind-driven induction generator and dc microgrid. Induction generator is being worked in self-energized mode with excitation capacitor at stator. The output current i.e., dc grid current act as a control variable to track the MP in the proposed WECS. In this manner, the proposed calculation for maximum power point tracking (MPPT) is autonomous of the machine and wind-turbine parameters. Further, a technique has been created for deciding the obligation proportion of the dc-dc converter for working the proposed system in MPPT condition utilizing wind turbine qualities, relentless state proportionate circuit of prompting generator and power balance in power converters. Circuit straightforwardness and basic control calculation are the significant points of interest of the proposed setup for supplying energy to the dc microgrid from WECS. The fruitful working of the proposed calculation for Fuzzy logic based MPPT has been shown with broad exploratory results alongside the simulated values.